2004
DOI: 10.1177/1476718x04042974
|View full text |Cite
|
Sign up to set email alerts
|

How Do they Manage?

Abstract: This article presents the findings from a review of literature on leadership in early childhood (EC). It identifies a paucity of research, despite a high potential for leadership activity in the early childhood field. It concludes that there is a clear need to identify what effective leadership practice is in terms of processes and outcomes within this field. It also concludes that theoretically based studies that allow different models and characteristics to be empirically tested are long overdue. The serious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(47 citation statements)
references
References 8 publications
2
41
0
4
Order By: Relevance
“…Therefore, our study highlights the need for the re-imaging of leadership which promotes partnerships with children and families and is consistent with findings from Burgess and Fleet (2009). Clearly, additional research is needed that focuses on community leadership in the early childhood field, which according to Muijs, Aubrey, Harris & Briggs (2004) is simply not available.…”
Section: Perceptions Of Leadershipsupporting
confidence: 60%
See 1 more Smart Citation
“…Therefore, our study highlights the need for the re-imaging of leadership which promotes partnerships with children and families and is consistent with findings from Burgess and Fleet (2009). Clearly, additional research is needed that focuses on community leadership in the early childhood field, which according to Muijs, Aubrey, Harris & Briggs (2004) is simply not available.…”
Section: Perceptions Of Leadershipsupporting
confidence: 60%
“…This demonstrates there is work to be done in building infrastructure between school, family and community. What is evident from the literature is that there has been little movement or improvement in the last 10 years in the development of leadership capacity for those early childhood educators in school settings (Muijs, Aubrey, Harris & Briggs, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although within a grantee's jurisdiction more effective center directors may be paid more, when examining data nationally, we cannot assume that all highly paid directors in urban areas with high costs of living are more effective managers than their rural peers Another reason for the lack of associations may be that the characteristics captured in these scales of challenges and supportive techniques are not telling the whole story. There have been calls for research to identify what effective center director management practices look like in the early childhood field (Muijs, Aubrey, Harris, & Briggs, 2004). Still, the majority of research on early childhood leadership has focused on more tangible aspects of program administration, including compliance with health, safety, legislative, and contractual requirements; coordinating family and social services; and financial management (e.g., Osgood & Stone, 2002).…”
Section: Predictors Of Emotional Supportmentioning
confidence: 99%
“…Some studies have shown how the quality of programmes and services for young children and their families is related to effective leadership by those in management positions (Rodd 1994, Stipek and Ogana 2000, Muijs et al 2004 but studies in this area remain few. Similarly, the concept of leadership in early childhood "remains weakly theorised, and resources to support and inform a distinctive early childhood leadership culture are sparse" (Woodrow and Busch 2008:83) .Generic management skills are offered but with little reference and understanding of this particular work environment.…”
Section: Management In the Early Years Sectormentioning
confidence: 99%